Kidney transplantation in the UK: a UK Transplant Registry analysis. (2nd January 2019) - Pankhurst, Laura; Robb, Matthew; Mumford, Lisa
Abstract : In this article, Laura Pankhurst et al report key figures about kidney transplantation in the UK, including information on the transplant list, transplant activity and survival after kidney transplant for all 24 centres performing kidney transplantation. Data were obtained from the UK Transplant Registry on kidney transplant activity between April 2008 and March 2018